Sleep apnoea is associated with hearing impairment: The Paris prospective study 3. (22nd May 2020) - Lisan, Quentin; van Sloten, Thomas; Climie, Rachel E.; Boutouyrie, Pierre; Guibout, Catherine; Thomas, Frederique; Danchin, Nicolas; Jouven, Xavier; Empana, Jean‐Philippe
Abstract: Objectives: Hearing impairment (HI) is a leading impairment worldwide, and identifying modifiable risk factors of HI may have major public health implications. The aim of this study was to investigate the association between obstructive sleep apnoea (OSA) and HI. Design: Observational longitudinal study (the Paris Prospective Study 3). Setting: Population‐based. Participants: Volunteers aged 50‐75 years and consulting at a preventive medical centre were included between 2008 and 2012. 6797 participants were included in the present analysis. Main outcome measures: Audiometry testing was performed in both ears in all participants, and HI was defined by a pure‐tone average (PTA) >25 decibels (dB) hearing level in the better ear. Results: Obstructive sleep apnoea (estimated by the Berlin questionnaire) was present in 18.6% (n = 1267) and HI in 13.9% (n = 947) of the participants. Mean age was 59.5 years (SD 6.2) and 63.5% were male (n = 4317). In multiple logistic regression modelling, OSA was significantly associated with a 1.21‐increased odds of HI (95% confidence interval 1.01‐1.44). Several sensitivity analyses supported this finding. Conclusion: Obstructive sleep apnoea is associated with a 21% increased odds of HI. These results support active screening of HI in subjects with OSA, and future studies should evaluate whether the treatment of OSA can delay the onset of HI.